Growth and yield of sunflower (Helianthus annus L.) as influenced by nitrogen, sulphur and farmyard manure under temperate conditions (SAARC Journal of Agriculture, 2014)
A field experiment was conducted at the Research farm, Division of Agronomy, Sher-e-Kashmir University of Agricultural Sciences and Technology, India for two consecutive rainy (kharif) seasons of 2009 and 2010 to find out the impact of nitrogen, sulphur and farmyard manure (FYM) on growth and yield of sunflower (Helianthus annuus L.). Application of 120 kg N ha-1 significantly increased all the yield components viz., plant height, leaf area index, dry matter production, capitulum diameter, achenes capitulum-1 and 1000-seed weight. Pooled yield increased by 26% with 120 kg N but it was statistically at par with 80 kg N ha-1. With increased N dose, the oil content consistently decreased but the oil yield improved during both years. Sulphur application at the rate of 60 kg ha-1 significantly increased plant height, leaf area index and dry matter production after 25 days of sowing (DAS). All yield contributing characters viz., filled achenes capitulum-1, head diameter and 1000-seed weights were higher with 60 kg S ha-1 over 30 kg S ha-1. Seed and stalk yield with 60 kg S ha-1 were significantly higher than those of 30 kg S ha-1. Similarly, oil content and oil yield with 60kg Sha-1 was 2 and 10.5 % over 30 kg S ha-1. Application of FYM at the rate of 10 and 20 t ha-1 was at par with each other but recorded significant improvement in the plant height, leaf area index and dry matter production of sunflower after 25 days of sowing over no FYM. FYM @10 and 20 t ha-1 increased the oil yield by 11 and 5.4 %, respectively over no application. DOI: http://dx.doi.org/10.3329/sja.v11i1.18386 SAARC J. Agri., 11(1): 81-89 (2013)